Pengenalan Beberapa Komponen Elektronika Dasar dan Aplikasinya di Lingkungan Sekitar Sebagai Upaya Menumbuhkan Minat pada Bidang Elektronika dan Teknologi - Hadi Imam Sutaji; Ali Warsito (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
Electronics and technology are inseparable from students' activities at school as well as their lives as children in the family environment. As part of technology, electronics also continues to developments in many ways in various fields, one of the which is manifested in electronic circuit systems. So that it functions as it should, the use of electronic components is very important on the electronic circuit system. Therefore, theory and introduction to basic electronic components and their applications in the surrounding environment need to be carried out by students. The purpose is to grow a sense of interest as motivation to develop potential, talent and interest in the field of electronics in particular and technology in general so that in the future it is hoped that students will not only become users but are also expected to become inventors, developers and innovators in the field of electronics and technology.